KORELASI KADAR KOLESTEROL DENGAN KEJADIAN DIABETES MELLITUS TIPE 2 PADA LAKI-LAKI - Anggraini, Rahayu (Jurnal Ilmu Kesehatan dan Kesehatan, 2018)
Abstract: Type 2 diabetes is one of the most common chronic diseases in the world. It is estimated thatmore than 140 million people worldwide are currently suffering from diabetes, and by 2025, anestimated more than 300 million people will suffer from the disease. The purpose of this study was toevaluate the correlation of cholesterol with the incidence of Diabetes Mellitus disease. The type of thisresearch is observational with cross-sectional analytic approach and done in PLN employees, total are112 people of which are mens. All participants underwent biochemical analysis of fasting blood sugar(BSN) and 2 hours PP (post prandial), and total cholesterol level test. Determination of glucose byglucose oxidase method and cholesterol level by CHOD-PAP method. The mean results in normalcholesterol (< 200 mg/dl) obtained BSN = 73 mg / dl, 2 Hours PP = 92 mg / dl, and in abnormalcholesterol (> 200 mg/dl) mean BSN = 81 mg / dl, 2 hours PP = 109 mg / dl, in independent T test withp = 0001 in both groups of different cholesterol levels. Results of the Pearson's correlation test, therewas a significant positive correlation between GDP and cholesterol levels (r = 0.262, p = 0.005), and 2hours PP and cholesterol levels (r = 0.258, p = 0.006). Conclusions: There was a significant positivecorrelation between 2 hours PP and cholesterol levels. This study shows there is a correlation ofcholesterol levels that develop diabetes mellitus type 2.